ESR studies of nitrogen atoms stabilized in aggregates of krypton–nitrogen nanoclusters immersed in superfluid helium - Mao, S.; Boltnev, R.E.; Khmelenko, V.V.; Lee, D.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Impurity–helium condensates (IHCs) containing nitrogen and krypton atoms immersed in superfluid 4Hehave been studied via a CW electron spin resonance (ESR) technique. The IHCs are gel-like aggregates of nanoclusters composed of impurity species. It was found that the addition of krypton atoms to the nitrogen–heliumgas mixture used for preparation of IHCs increases efficiency of stabilization of nitrogen atoms. We haveachieved high average (5·1019 cm–3) and local (2·1021 cm–3) concentrations of nitrogen atoms in kryptonnitrogen–helium condensates. The analysis of ESR lines shows that three different sites exist for stabilization of nitrogen atoms in krypton-nitrogen nanoclusters. Nitrogen atoms are stabilized in the krypton core of nanoclusters, in the nitrogen molecular layer which covers the Kr core and on the surface of the nanoclusters. High concentrations of nitrogen atoms achieved in IHCs provide an important step in the search for magnetic ordering effects at low temperatures.